Introduction to concept mapping in nursing : critical thinking in action - Schmehl, Patricia (Burlington, Massachusetts : Jones & Bartlett Learning, 2014)
Introduction to Concept Mapping in Nursing provides the foundation for what a concept map is and how to create a map that applies theory to practice. This excellent resource addresses how students will think about applying nursing theory as it relates to concept mapping. This book is unique because it focuses on a broad application of concept mapping, and ties concept mapping closely to critical thinking skills. Furthermore, this book will prepare nursing students to learn how to map out care plans for patients as they talk with patients
1. Understanding concept mapping -- 2. Map components and basic formatting -- 3. Advanced concept map formatting -- 4. The data gathering process -- 5. Constructing a concept map -- 6. Methods of map composition -- 7. Use of concept maps in nursing -- 8. Other educational uses for concept maps
Includes bibliographical references and index
Keywords: Concept Formation; Education, Nursing -- methods; Learning; Models, Nursing; Nursing Theory; Nursing -- Study and teaching; Teaching -- Methods